PROSPECTIVE BASIC CLINICAL AUDIT USING MINIMAL CLINICAL DATA SET - Ali, Syed Asad; Soomro, Abdul Ghani; Tahir, Syed Muhammad; Memon, Abdul Sattar (Journal of Ayub Medical College Abbottabad, 2010)
Background: Audit is a means of quality control for medical practice by which the profession should regulate its activities with intention of improving overall patient care. Objective of this study was to report 1 year basic clinical audit of a general surgical ward and comparison of results with available data. Methods: All patients admitted and managed in Department of Surgery Unit-II, Liaquat University Hospital, Jamshoro/Hyderabad from January to December 2007 were included in the study for basic clinical audit. Data of all surgical patients admitted during this period were retrieved from the departmental register. Details of surgical procedures and complications were recorded from the patients’ charts. Results: Total number of patients was 1434, out of which 844 (58.85%) were males and 590 (41.14%) were females. Majority (70.02%) of the patients were between 16 to 50 years of age. Elective surgeries were performed in 487 (33.74%) and emergency surgeries in 430 (29.79%) cases, whereas rest of the 526 patients (36.28%) were managed conservatively. Consultant was the primary surgeon in less than 50% of the procedures compare to post graduate trainees and registrars. The most common surgeries performed in elective wing were inguinal hernia repairs (25.66%) and cholecystectomies (22.99%). In emergency wing, most of the surgeries were exploratory laparotomies (38.13%) and appendicectomies (22.79%). Average duration of hospital stay in elective wing was 1-10 days and in emergency wing it was 2-21 days. There was an overall complication rate of 6.3% and a mortality rate of 2.44% respectively. Conclusion: We conclude that surgical audit has potential benefits for patients, clinicians, and provision of services for a continuous education, research and improved practice habits and should be perform on yearly basis. We also recommend the proper computerised audit programs and committees for its monitoring and evaluation. Keywords: Clinical Audit, Surgery, Outcome